Labour Force Participation and Employment of Humanitarian Migrants: Evidence from the Building a New Life in Australia Longitudinal Data - Zhiming Cheng; Ben Zhe Wang; Lucy Taksa (Global Labor Organization (GLO), 2017)
This study uses the longitudinal data from the Building a New Life in Australia survey to examine the relationships between human capital and labour market participation and employment status among recently arrived/approved humanitarian migrants. It includes attention to the heterogeneity of labour force participation and employment status across genders and also migration pathways. We find that the likelihood of participating in the labour force is higher for those who had preimmigration paid job experience, completed study/job training and have job searching knowledge/skills in Australia and possess higher proficiency in spoken English. We find that the chance of getting a paid job is negatively related to having better pre-immigration education, but it is positively related to having unpaid work experience and job searching skills in Australia, and better health.
Keywords: J15; J21; J24; 330; Australia; humanitarian migrant; human capital; labour force participation; employment status